Desenvolvimento de um programa de intervenção cognitiva para idosos - Mariana Teles Santos (2015)
The field of cognitive intervention for elderly presentes multiple paths and also several challenges. The theoretical advance of this area depends on the construction and research of new training programs in order to contribute to the evidences about the possibility of change in cognition in old age. This research aimed to construct a cognitive training for healthy elderly (without dementia diagnosis), in individual mode, pencil and paper format, focusing on stimulation of cognitive skills such as attention, processing speed, episodic memory and memory work. After the development of training tasks, two preliminary studies tested the protocol. The first was conducted in a female participant (89 years) and contributed to a qualitative analysis program, resulting in the final version. The second pilot study had fifteen participants, seven experimental group (EG), aged between 70 and 82 years (M = 73.57, SD = 4.11) and average study of 5.8 years (SD = 1.02); and eight participants in the control group (CG), aged 69-77 years (M = 74,00, SD = 4.58), and average study of 2.88 years (SD = 2.58). The final survey sample was expanded to 80 participants (N = 80): the EG (N = 47) had a mean age of 69.66 years (SD = 7.51) and average study of 7.06 years (SD = 5.42); and the CG (N = 33) had a mean age of 69,73 (SD = 7,45), and average study of 7,06 years (SD = 5,42).The cognitive measures used were: Episodic Memory Test (list and history) and six subtests of the WAIS-III: Complete Figures, Codes, Arithmetic, Matrix Reasoning, Digits and Symbols Search. The instruments were applied before (pre-test) and after training (post-test). The training was conducted in individual sessions, lasting 10-14 meetings, each meeting lasting 1h30m and weekly frequency. The results of the rank transformation ANOVA indicated a significant effect of training for: Complete Figures (F(74) = 14,88, p = 0,0002, d = 0,90, cles = 73,69%), Codes (F(74) = 5,66, p = 0,019, d = 0,55, cles = 65,21%) and Digits(F(74) = 5,38, p = 0,02, d = 0,54, cles = 64,85%). For the other measures were not observed training effects. The results show that the EG compared to the CG, showed significant increase in their cognitive performance after training for attention skills, processing speed, episodic memory and categorization (distinction between essential and non-essential details). This effect was captured by three of the eight cognitive measures used.